Mirtazapine in comorbid major depression and an alcohol use disorder: A double-blind placebo-controlled pilot trial. (30th August 2016) - Cornelius, Jack R.; Chung, Tammy; Douaihy, Antoine B.; Kirisci, Levent; Glance, Jody; Kmiec, Julie; FitzGerald, Douglas; Wesesky, Maribeth A.; Salloum, Ihsan
Abstract: This was a first double-blind, placebo-controlled pilot study to evaluate the efficacy of the novel antidepressant medication mirtazapine for treating both the depressive symptoms and the level of alcohol consumption of subjects with comorbid major depressive disorder and an alcohol use disorder (MDD/AUD). The results of two previous studies of mirtazapine in MDD/AUD subjects had suggested efficacy for mirtazapine for decreasing their level of depressive symptoms, but level of alcohol consumption had not been assessed in those studies. All subjects in this 12-week pilot study were randomized to either mirtazapine or placebo, and also received motivational enhancement therapy. Between-group analyses involving the outcome measures of depressive symptoms, level of alcohol consumption, and level of alcohol craving indicated no significant differences between groups, possibly because of limited sample size. However, within-group t tests in the mirtazapine group showed a significant decrease in depressive symptoms by week 2, also noted at all subsequent assessments (weeks 3, 4, 6, 8, 10, and 12) during the 12-week study. In contrast, no significant decrease in depressive symptoms was noted in the placebo group until week 8. No evidence of efficacy was found for mirtazapine for decreasing level of alcohol consumption in MDD /AUD subjects. Highlights: A first study to assess the efficacy of mirtazapine for treating MDD/AUD. Mirtazapine was well tolerated in the study. No significant differences between the treatment groups were noted for any outcome. Within group results suggest efficacy for mirtazapine for decreasing MDD symptoms. No evidence for mirtazapine decreasing alcohol consumption was found.